Environmental and Economic Impact of Carbon Credit in Makassar City in Indonesia - Yuzuru Miyata; Hiroyuki Shibusawa; Takahide Fukuda (European Regional Science Association (ERSA), 2015)
Economic measures are advanced to environmental problems in EU nations. The economic approach imposes a constant economic load on activities negatively affecting the environment, and it is also a technique for giving a constant profit for activities conserving the environment. The whole society is expected to be environmental-friendly state by this incentive. Moreover, this method has the advantage for inventing new technologies and efficient production processes. The direct regulation is pointed out as an environmental conservation measure. However dependence on the regulatory control has the anxiety to decline the economic vitality of firms. Therefore, the economic approach that does not decrease inventiveness and the autonomy of each firm becomes important. Carbon credit can be taken as one of the economic measures for controlling global warming. The upper limits of CO2 emissions are assigned to each firm or country, and the carbon credit is defined as a credit of the volume of CO2 emissions generated by economic activities. The mechanism in which the total CO2 emission is controlled by buying and selling the carbon credit is called emission right trading. The present study focusses on the carbon credit. Although researches on environmental and economic impact by carbon credit at a country level have already been conducted, studies on such a topic in developing countries emitting large CO2 and/or a city level have hardly been found. Hence, the present study analyzes the environmental and economic impact of introduction of carbon credit in Makassar City, which is a main city in east Indonesia, by employing a computable general equilibrium (CGE) model. The reason selecting Indonesia as a study country is that CO2 emissions in Indonesia considering the swiddens and the peaty land are ranked at the third place in the world. The reason selecting Makassar City as a study region is that there is an enough forest in surroundings of Makassar City and a big amount of the CO2 forest absorption can be expected for issuing the carbon credit. Moreover, it is another reason that there is an input-output table in Makassar City, and data that is necessary to construct a computable general equilibrium model is available. In this paper, Makassar City is assumed to issue a carbon credit and sell it to other regions. Numerical simulations are implemented to analyze the environmental and economic impact of the carbon credit. The simulation results show a decrease in CO2 emissions and an increase in household utility in Makassar City by selling the carbon credit to other regions.
Keywords: Q50; Q53; Q54; Q56; Q58; 330; carbon credit; global warming; Makassar; Indonesia; CGE